Pengembangan Produk Bakso yang Berbahan Baku Tanaman Berantioksidan - Wellyalina Wellyalina; Daimon Syukri (Politeknik ATI Padang, 2020)
The development of functional food is increasing. Meatball is one of popular food product that can be developed to become more functional by adding antioxidant. Meatballs are processed products from small round meat. The aim of this study was to obtain the best formula for meat ball production with high antioxidant and also have good organoleptic characteristics. The addition of Moringa leaves, celery,cup leaves panax, and lime leaves to the original formula of meat ball production were used as the treatments in this study. The results indicated that the addition of cup leaves panax could produce the functional meat ball with the highest antioxidant and best organoleptic characteristics among all treatments.